2012
DOI: 10.1051/0004-6361/201116848
|View full text |Cite
|
Sign up to set email alerts
|

Physical studies of 81P/Wild 2 from the last two apparitions

Abstract: Context. We downloaded data for the comet 81P/Wild 2 for May and June 2004 from the ESO archive and monitored this comet from January to August 2010 during its 6th perihelion passage since its discovery in 1978. Photometric data were used to monitor the comet's gas and dust activity as a function of heliocentric distance. Non-photometric data were used for an analysis of the evolution of the dust coma morphology. Aims. The goal of the analysis of the observational data was to characterize the evolution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…Over the past four years we have developed a model of dust coma structures, aiming at simulating the behavior of dust jets from the subsurface of cometary nuclei up to thousands of kilometers away from the surface. Our model was used successfully to study several targets: 73P/Schwassmann-Wachmann 3 (Vincent et al 2010a), 9P/Tempel 1 (Vincent et al 2010b), and 81P/Wild 2 (Lin et al 2012). For the last two targets, we have reproduced the behavior of the jets from ground-based observations only, with results that agree with in situ measurements by the Deep Impact and Stardust spacecrafts.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Over the past four years we have developed a model of dust coma structures, aiming at simulating the behavior of dust jets from the subsurface of cometary nuclei up to thousands of kilometers away from the surface. Our model was used successfully to study several targets: 73P/Schwassmann-Wachmann 3 (Vincent et al 2010a), 9P/Tempel 1 (Vincent et al 2010b), and 81P/Wild 2 (Lin et al 2012). For the last two targets, we have reproduced the behavior of the jets from ground-based observations only, with results that agree with in situ measurements by the Deep Impact and Stardust spacecrafts.…”
Section: Introductionmentioning
confidence: 53%
“…However, a full understanding of the origin of these collimated outflows is not required to perform simulations at the scale of our observed images. As we have shown in Vincent et al (2010b) and Lin et al (2012), good approximations of the initial size and velocity distributions of the particles are sufficient to fully reproduce the behavior of the jets. Thus our model does not simulate the initial acceleration phase of the dust particles when they are lifted from the surface and accelerated by the gas.…”
Section: Activity Modelmentioning
confidence: 86%
See 1 more Smart Citation
“…A reddening between 5 and 12%/1000 Å was found by Lin et al (2013) for comet Hartley 2. Lin et al (2012) found that comet 81P/Wild 2 was redenned by approximately 8.2-8.6%/1000 Å. Dust reddening for comet C/2000 WM1 was also around the same value (Lara et al 2004).…”
Section: Dust: A(θ)fρ Spatial Profiles and Dust Colormentioning
confidence: 88%
“…This is the first time that a spiral structure was seen in the near-coma region of a comet, and it was made possible by the close distance of the Rosetta spacecraft to the comet nucleus. Nevertheless, from groundbased observations (Samarasinha & A'Hearn 1991;Lin et al 2007Lin et al , 2012Lin et al , 2013, we also saw a repeated curved appearance of the gaseous and dust jets that was related to the rotation of the nucleus. The curved appearance of the jets might also have been caused by solar gravity and radiation pressure.…”
Section: Introductionmentioning
confidence: 85%